2020
DOI: 10.1017/cem.2019.480
|View full text |Cite
|
Sign up to set email alerts
|

CAEP 2019 Academic Symposium: Got competence? Best practices in trainee progress decisions

Abstract: BackgroundCompetence committees play a key role in a competency-based system of assessment. These committees are tasked with reviewing and synthesizing clinical performance data to make judgments regarding residents’ competence. Canadian emergency medicine (EM) postgraduate training programs recently implemented competence committees; however, a paucity of literature guides their work.ObjectiveThe objective of this study was to develop consensus-based recommendations to optimize the function and decisions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This study also identified variability in CCs’ abilities to maintain capacity among their members, which is aligned with the longstanding tension between resident education and service provision that has been reported in the literature 42,43 . This suggests a need to develop strategies for rewarding and managing faculty workload, including assigning merit points for individuals who serve on CCs, assigning a set number of reviewers per file, having members come to meetings having pre‐reviewed their files to increase efficiency, and where possible, rotating members on a regular basis 13,14,36 …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This study also identified variability in CCs’ abilities to maintain capacity among their members, which is aligned with the longstanding tension between resident education and service provision that has been reported in the literature 42,43 . This suggests a need to develop strategies for rewarding and managing faculty workload, including assigning merit points for individuals who serve on CCs, assigning a set number of reviewers per file, having members come to meetings having pre‐reviewed their files to increase efficiency, and where possible, rotating members on a regular basis 13,14,36 …”
Section: Discussionsupporting
confidence: 61%
“…Previous literature on group decision making has identified the importance of diverse committee membership in ensuring robust decision‐making processes, as this enables data to be considered from multiple lenses and helps reduce groupthink 7,11,13,36 . Nevertheless, the findings of the present study suggest that optimising CC membership is not always a simple task.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Even if we are able to significantly improve the usefulness of supervisor comments within a program, the trend of using increasing amounts of qualitative data brings on new challenges; narrative comments will take more time to analyze and integrate, and they will require skills that current faculty may not possess. 23,24 Given the importance of having useful supervisor narrative comments within CBME, 1,2 and that the QuAL demonstrates validity evidence for measuring utility, it is a tool that can serve multiple purposes. One aspect of potential program evaluation in CBME is to determine whether or not the narrative comments in a program or at an institution meet a certain standard over time.…”
Section: Discussionmentioning
confidence: 99%
“…Even if we are able to significantly improve the usefulness of supervisor comments within a program, the trend of using increasing amounts of qualitative data brings on new challenges; narrative comments will take more time to analyze and integrate, and they will require skills that current faculty may not possess. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%